Users’ Behavior of Identity Protection and Online Data Security Management - Balraj, Noah Anburaj; Kirilov, Stanislav (8ISC Proceedings: Technology; 8ISC Proceedings: Technology, 2022)
The objective of this study was to understand the user’s IT knowledge to account and data management practices related to personal, social, and business. Internet is global and the vulnerability is global too. The Internet has become part of the people who are engaged with it. The purpose of the study was to learn the level of users’ IT knowledge through the account, identity protection, and online data management practices to understand the relationship and design the needed programs to enhance their knowledge for better protection. With the increase in users of mobile phones, laptops, desktops emerge issues and development measures. The identified gap was between the users’ IT knowledge and their practices on account and data management. This gap was identified to help design programs to help the users to develop strategies through various alternatives to prevent identity and data theft. The population of data was collected in AIU for strengthening in protecting identity theft and data theft of our faculty members, staff members, students, and other stakeholders. Two samples Chi-Square was used for the analysis of data for the rejection or acceptance of null or alternate hypotheses based on critical value using Microsoft excel. The analysis was individually done for all the 27 factors considered in this research. Results show eight factors had a significant relationship, and 19 factors do not significantly relate between users’ IT knowledge and data management and practices. A follow-up study will be conducted on the sub-ordinate level of users’ behavior and practice of identity theft and data protection. Keywords : User experience, identity protection, online data management and practices